Development and Quality Evaluation of Canned Pineapple (Journal of Environmental Science and Natural Resources, 2018)
The study was done to investigate the chemical constituents of a developed canned pineapple (Ananas comosus) product and to evaluate the microbiological quality of the product. A water bath canner and quart glass jars equipped with cap having top rubber were used for canning of pineapple (A. comosus). The thermal processing was done for the canning of pineapple. The raw fresh pineapple and canned pineapple were analyzed for their moisture content, ash, fat, crude fiber and protein contents. The moisture content, ash content, fat, crude fiber, protein content of fresh pineapple were 81.5%, 0.38%, 0.2%, 1.4% and 0.5%. The moisture content, ash content, fat, crude fiber and protein content of canned pineapple were 70%, 0.35%, 0.4%, 1.9% and 1.5% respectively. These Chemical constituents of the canned pineapple were almost similar with the raw fresh pineapple except the crude fiber and protein. The yeast and mould present in the product were also counted by using PDA (potato dextrose agar). The yeast and mould count for the product was within the consumer safety limit.J. Environ. Sci. & Natural Resources, 10(2): 183-187 2017